MANAJEMEN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU DI WILAYAH KOTA LHOKSEUMAWE - Fitriana (Majelis Pendidikan Aceh, 2022)
This report examines principal management as the planning, implementation, and management of the entire school in order to improve teacher performance effectively and efficiently. This study aims to identify the Planning, Implementation, and Monitoring of the essential supporting components. In this study, qualitative methods and descriptive analysis were employed to obtain the results of the principal management analysis. Principals, vice principals, teachers, Pokja Guru leaders, and supervisors are included. The analysis technique involves observation, interviews, and documentation. Methods of planning and managing teacher activities, organizational strategies to increase teacher activities, implementation strategies for improving teacher performance, and strategies for monitoring teacher performance are among the findings of this research analysis. The study revealed that principal management is necessary as a strategy for achieving school goals, with the shared desire of all school components to successfully complete processes affecting students and teachers as the central theme.